Dietary supplementation of Astragalus polysaccharide or its nanoparticles enhances testicular hemodynamics, echotexture, scrotal circumference, concentration of testosterone, estradiol, nitric oxide, and total antioxidant capacity, and semen quality in mature Ossimi rams - Eman Fayez; Ali Salama; Mohamed Ahmed Ismail; Fady Sayed Youssef; Zaher Mohamed Rawash; MR Oshba; Haney Samir (BMC Veterinary Research)
Abstract This study investigated, for the first time, the potential role of Astragalus polysaccharide (APS) and APS nanoparticles on testicular blood flow (TBF) and semen quality in Ossimi rams. Fifteen sexually mature Ossimi rams were allocated randomly into two treated groups that orally administered either nano APS (2 g/ram/day; n = 5) or APS (20 g/ram/day; n = 5) for four weeks and a control group (n = 5). The nano-emulsion was prepared by adding corn oil to the APS solution, sonicated, centrifuged at 20,000 rpm, then washed 3–4 times, and vacuum dried overnight at 40 °C. The antioxidant activity of APS and APS nano-emulsion was evaluated in vitro. Blood collection and ultrasonographic assessment of the testes and supratesticular arteries (STAs) were conducted immediately before treatment (W0) and once weekly for 6 successive weeks after APS and nano APS administration (W1-W6). Serum testosterone (T) and estradiol (E2) concentrations were determined by ELISA kits, while nitric oxide (NO) and total antioxidant capacity (TAC) were measured spectrophotometrically. Moreover, semen collection and evaluation of some sperm parameters were performed once a week. Results revealed decreases (P < 0.05) in the Doppler indices (resistive index; RI, pulsatility index; PI, and systolic/diastolic; S/D) of the testicular arteries at most time points of the study in the nano APS and APS groups. Pixel intensity (PIX) and integrated density (IND) of testicular parenchyma were significantly reduced (P ˂ 0.05) in the treated groups compared to the control one. T, E2, NO, and TAC concentrations increased (P < 0.05) in the treated groups compared to the control one. Increases (P < 0.05) were noticed in the mass motility, progressive motility %, live sperm %, and membrane integrity % in nano APS and APS groups, compared to the control. Rams in the nano APS group had significantly higher (P < 0.05) sperm cell concentration than the control one. In conclusion, this study extrapolated that the dietary administration of APS and its nanoparticles can improve TBF, testicular echotexture, sperm characteristics, and the concentration of serum T, E2, NO, and TAC with a more significant effect in the APS nanoparticles compared with APS. So, it could be recommended as a dietary supplementation (2 g/ram/day) for enhancing the reproductive performance of rams.